Breve til og fra Grundtvig, marts - juni 1844 - Holm, Jette (Grundtvig-studier, 2005)
Breve til og fra Grundtvig, marts-juni 1844[Letters to and from Grundtvig, March-June 1844]By Jette Holm Gr’s letters from the end of March through to June 1844 cover the period in which he was seriously ill with the after-effects of mumps and severe depression. They were published in Breve fra og til N. F. S. Grundtvig (BG II), Peter Rordam, 1, Blade a f hans Levnedsbog og Brevvexling fra 1806-1844 [Leaves from his biography and correspondence] (Rørdam 1891); and Gunni Busck, et Levnedslob i en Prastegaard [A lifetime in a vicarage] (Bech 1878). However, the Registrant (Catalogue of mss in the Grundtvig Archive, Copenhagen) lists further letters not yet in print. One single letter is found outside the Archive, in the Royal Library’s Ny kongelig Samling (NKS). In order to complete the picture of the course of Gr’s illness in 1844, the unprinted letters relating to the illness and Gr’s visits to clerical friends are presented here. Jørgen Ertner, in Et ord a f Guds Son [A saying of the Son of God] (Ertner 1997, 185 ff.) has produced a hitherto unknown letter from Gr to Ferdinand Fenger, dated 28 May 1844. The letter is there thoroughly discussed, but for the sake of completeness it is included in the present gathering of unprinted letters from that period. The letters presented here are also offered as documentation of Christian Thodberg’s article on Gr’s crisis of Spring 1844.